Compensation in practice : the foundation 'Remembrance, Responsibility and Future' and the legacy of forced labour during the Third Reich - Goschler, Constantin 1960- HerausgeberIn; Brunner, José 1954- MitwirkendeR; Ruchniewicz, Krzysztof 1967- MitwirkendeR; Ther, Philipp 1967- MitwirkendeR; Stiftung Erinnerung, Verantwortung und Zukunft (Berghahn Books, 2017)
Inhaltsverzeichnis: Introduction / Constantin Goschler -- The long shadow cast by Nazi forced labour : changing concepts of compensation and definitions of persecutees since 1945 / Henning Borggräfe -- The foundation "Remembrance, Responsibility and Future" 1999-2007 : the final chapter of compensation for Nazi injustice? / Benno Nietzel -- The Jewish Claims Conference and compensation for Nazi forced labour 1951-2008 / Benno Nietzel -- Compensating the rest of the world : the International Organisation for Migration (IOM) / Paul Erker -- The forced labourer payments programme in Poland : practices and perceptions / Michael Esch -- Compensation for forced labourers in the Czech Republic / Stephanie Zloch -- "We cannot allow the words of apology to sound only on gravestones" : forced labourer compensation in the Ukraine / Julia Landau -- Compensation for Nazi forced labour in post-Soviet Russia and Belarus / Tanja Penter --